2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6385649
|View full text |Cite
|
Sign up to set email alerts
|

Embodied hyperacuity from Bayesian perception: Shape and position discrimination with an iCub fingertip sensor

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…A strength of the formalism is that it connects closely with leading work in neuroscience, allowing insights from animal perception to be transferred to robot perception. For example, these methods have enabled the first demonstration of hyperacuity in robot touch [9], giving perceptual acuity finer than the sensor resolution, as is common in animal perception. That study also found that active perception helped the hyperacuity, although those methods do suffer from being somewhat ad hoc by not making best use of the 'where' and 'what' aspects of the problem.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A strength of the formalism is that it connects closely with leading work in neuroscience, allowing insights from animal perception to be transferred to robot perception. For example, these methods have enabled the first demonstration of hyperacuity in robot touch [9], giving perceptual acuity finer than the sensor resolution, as is common in animal perception. That study also found that active perception helped the hyperacuity, although those methods do suffer from being somewhat ad hoc by not making best use of the 'where' and 'what' aspects of the problem.…”
Section: Related Workmentioning
confidence: 99%
“…Our algorithm for active perception is based on including a sensorimotor feedback loop in an existing method for passive Bayesian perception [9,12]. Both methods assume that the sensor makes a discrete contact measurement (here a tap) onto an object, from which the joint likelihoods of object location and identity are used to update the posterior beliefs for those perceptual classes.…”
Section: Active Bayesian Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of papers [4], [5], [6], [7], [8], we have formalized a Bayesian perception approach for robotics based on this recent progress in understanding animal perception. Our formalism extends naturally to active perception, by moving the sensor with a control strategy based on evidence received during decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the belief threshold has been treated as a free parameter that adjusts the balance between mean errors and reaction times (e.g. [7,Fig. 5]).…”
Section: Introductionmentioning
confidence: 99%